An annotated checklist of the Iranian Dasytidae and Rhadalidae (Coleoptera: Cleroidea) - Plonski, Isidor S.; Ghahari, Hassan (Zootaxa, 2018)
We herein provide an annotated checklist for the Iranian Dasytidae and Rhadalidae (Coleoptera: Cleroidea). A total of 54 species and three subspecies of Dasytidae in 16 genera, four tribes and three subfamilies, and 11 species of Rhadalidae in five genera and three subfamilies are reported and discussed where necessary. Of these, 27 (sub-) species of Dasytidae (48%) and eight species of Rhadalidae (73%) are currently known only from Iran, and are here considered as endemic species. However, some species occurences are doubtful or need confirmation. One species (Dasytes xanthocnemus Kolenati, 1846) is reported from Iran for the first time. Furthermore, Danacea micans astrabadensis Pic, 1922 is resurrected from synonymy and given subspecific status.